Hypothalamus Transcriptome Reveals Key lncRNAs and mRNAs Associated with Fecundity in Goats - Yingshi Wei; Caiye Zhu; Xiaoyun He; Mingxing Chu (Animals)
The hypothalamus (hyp) serves as the regulatory hub of the neuroendocrine system, synthesizing and secreting reproductive hormones that modulate estrus, follicular maturation, and embryonic development in goats. This study employed RNA-seq analysis to examine gene expression in the hypothalamic tissue of Yunshang black goats during the luteal phase in goats with high fecundity (LP_HY), during the luteal phase in goats with low fecundity (LP_LY), during the follicular phase in goats with high fecundity (FP_HY), and during the follicular phase in goats with low fecundity (FP_LY). Differential long non-coding RNAs (DE lncRNAs) and differential mRNAs (DE mRNAs) were subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses and the construction of co-expression networks associated with reproduction. As a result, DE lncRNAs (390, 375, 405, and 394) and DE mRNAs (1836, 2047, 2003, and 1963) were identified in the four comparisons, namely FP_LY vs. FP_HY, LP_HY vs. FP_HY, LP_LY vs. FP_LY, and LP_LY vs. LP_HY, respectively. Functional annotations indicated significant enrichment of numerous DE lncRNAs and DE mRNAs in reproduction-related pathways such as the gonadotropin-releasing hormone pathway, the prolactin signaling pathway, the estrogen signaling pathway, the Wnt signaling pathway, oocyte meiosis, and progesterone-mediated oocyte maturation. The co-expression network of lncRNAs and target genes identified the interrelationships between reproduction-related genes such as IGF1, PORCN, PLCB2, MAPK8, PRLR, and CPEB2 with our newly discovered lncRNAs. This study expands the understanding of lncRNAs and mRNAs in goat hypothalamic tissue and provides new insights into molecular mechanisms related to goat reproduction.